Mudanças socioambientais promovidas pelo turismo litorâneo em comunidades que dão acesso a parques nacionais - Pinho, Thays Regina Rodrigues (2019)
Tourism is a socioeconomic activity which provides local development and creates new socioenvironmental dynamics in Brazilians northeast coastal communities. Nowadays, the coastal area has become the main focus of touristic investments. In other hand, the economic overvaluation of tourism can involve negative effects such as mass tourism and touristification of spaces. Sustainable actions have been suggested and tested to restrain these adverse impacts in touristic communities on the coast. The construction of this thesis followed the theory of production of space applied on tourism and the touristification of spaces in natural areas. The main purpose of this study is to analyze the socioenvironmental changes provoked by the development of coastal tourism on two coastal communities nearby of the National Park of Jericoacoara and the National Park of Lençóis Maranhenses. The specifics objectives are to present the new configurations due to coastal tourism, to identify the factors which impacts on local sustainability and to analyze the management of protected spaces and these communities under the perspective of the growth of tourism. In order to accomplish this task, descriptive and analytical methodological practices were established, based on quali-quantitative approach with application of bibliographical and documentary research, production of primary data and fields observations. The primary data collect was based on systematic observations and semi-structured interviews with opened questions applied to tourism managers and protected areas managers. The data analysis was done by content analysis. The results show that the main socioenvironmental transformations in both communities, Jericoacoara/CE and Barreirinhas/MA, are related with new sociospaces configurations because of tourism exploration, represented by touristification and massification, and significative changes on community life. The management process of tourism and protected areas often reinforces the overvaluation of the activity and the touristification.